2016
DOI: 10.3390/ijms17030305
|View full text |Cite
|
Sign up to set email alerts
|

Key Immune Events of the Pathomechanisms of Early Cardioembolic Stroke: Multi-Database Mining and Systems Biology Approach

Abstract: While inflammation has generally been regarded as a negative factor in stroke recovery, this viewpoint has recently been challenged by demonstrating that inflammation is a necessary and sufficient factor for regeneration in the zebrafish brain injury model. This close relationship with inflammation suggests that a re-examination of the immune system’s role in strokes is necessary. We used a systems biology approach to investigate the role of immune-related functions via their interactions with other molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The role of YWHAZ gene was shown in several neurodegenerative diseases such as, Huntington’s disease, Alzheimer’s disease, and amyotrophic lateral sclerosis [89,90,91]. As we found in our bioinformatic analysis a similar study showed the importance of YWHAZ gene in CE [92]. Besides, the role of PIK3R1 gene in stroke is yet to be published.…”
Section: Bioinformatics Analysismentioning
confidence: 64%
“…The role of YWHAZ gene was shown in several neurodegenerative diseases such as, Huntington’s disease, Alzheimer’s disease, and amyotrophic lateral sclerosis [89,90,91]. As we found in our bioinformatic analysis a similar study showed the importance of YWHAZ gene in CE [92]. Besides, the role of PIK3R1 gene in stroke is yet to be published.…”
Section: Bioinformatics Analysismentioning
confidence: 64%
“…(2) we then constructed candidate GENs by using candidate PPI network and candidate gene/ miRNA/lncRNA regulatory networks (in infectious diseases, candidate interspecies cross-talk GEN is necessary); (3) we identified real GEN (or real interspecies GEN) of each stage of a disease by using the genome-wide high throughput data of the disease; (4) we then applied the principal network projection (PNP) method to extract the core nodes of GENs such as core proteins, genes, miRNAs, and lncRNAs to construct core GENs in different stages of a disease. [16][17][18][19] By comparing the core GENs between two connective stages of a disease and projecting them to KEGG pathways to get core signalling pathways of the disease, we then could extract differential core signalling pathways between different stages to get insight into pathogenic mechanism of the disease. Based on pathogenic mechanism, we could select multiple biomarkers for multiple drug targets to design multiple molecule drugs by applying drug database mining to CMAP and DGIdb databases for therapeutic treatment of the disease.…”
Section: Multiple Drug Targets Identification Via Systems Biology Methodsmentioning
confidence: 99%
“…A principal network projection (PNP) method is employed to extract core GENs from GENs based on the principal component analysis (PCA) of GENs in different stages of diseases. [16][17][18][19] Then we project the core GENs to KEGG pathways (i.e., denotation based on KEGG pathways) to obtain the core pathways from which we could investigate the pathogenic mechanism based the changes of core pathways of different stages of disease. We could identify some significant biomarkers for multiple drug targets based on pathogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Post-ischemic acute brain injury typically peaks within 24 h of the insult, and reaches its highest point within 48 h [ 149 ]. Due to this quick onset and short duration of acute brain injury, potential neuroprotective therapies need to be administered early, i.e., within 3–6 h of the onset.…”
Section: Cell Transplantation For Diseases Of the Nervous Systemmentioning
confidence: 99%